Ivestigation of Open Slot Lines with Semiconductor Substrates - Nickelson, L.; Tamošiūnienė, M.; Tamošiūnienė, M.; Ašmontas, S.; Ašmontas, S.; Tamošiūnas, S.; Tamošiūnas, S. (Elektronika ir Elektrotechnika, 2004)
In this paper we analyzed the open slot lines with n-Si substrates. The slot lines we ivestigated electrodynamically rigorously bymethod of singular integral equations. The algorithm enables one to take into account real sizes of slot lines. Dependences of thepropagation constant on the frequency for different slot lines were determined. We analized how the substrate thickness and width, theslot width, the strip conductor width and its placement on the substrate surface affected the number of modes propagating in the slot lineand what the geometric parameters of the line should be to ensure propagating of only one mode (this is important in practice). Ill. 8,bibl. 10 (in Lithuanian; summaries in Lithuanian, English, Russian).